Cyberbullying : what counselors need to know - Bauman, Sheri (Alexandria, Virginia : American Counseling Association, 2011)
This informative book offers complete, up-to-date coverage of the growing problem of cyberbullying. Written for counselors, teachers, school leaders, and others who work with children and teens, Cyberbullying addresses the real-life dangers students face on the Internet. Benefits and Features Discussion of the different types of cyberbullying and cyberbullying environmentsOverview of prominent theories of aggressive behaviorExamination of the developmental differences in cyberbullying and victimization across the life spanProactive responses to cyberbullyingEffective, nonpunitive strategies.
Introduction -- Conventional vs. cyberbullying -- Cyberenvironments -- Types of cyberbullying -- Theories of aggressive behavior -- Developmental factors in cyberbullying -- Strategies for prevention and reduction of cyberbullying -- Responding to cyberbullying -- Counseling strategies to combat cyberbullying -- Adult cyberbullying -- The role of counselors -- Additional resources -- Appendix: Cyberbullying research.
Includes bibliographical references (pages 173-192) and index.
Print version record.
Keywords: Cyberbullying; Cyberbullying -- Case studies; Bullying; Bullying; Cyberbullying -- Case studies; Cyberbullying; Electronic books; Case studies